Selected Metabolic Markers in Girls with Turner Syndrome: A Pilot Study - E. Błaszczyk; M. Lorek; T. Francuz; J. Gieburowska; A. Gawlik (International Journal of Endocrinology)
Background. Turner syndrome (TS) predisposes an individual to obesity and related metabolic disorders. As the TS population is at a higher risk of cardiovascular diseases and malformations, research into laboratory markers of metabolic complications has been ongoing. Special significance has recently been attributed to matrix metalloproteinases (MMPs), their inhibitors (TIMPs), and neurotrophic factors, such as BDNF and GDNF. Objective. To establish whether cardiometabolic risk in patients with TS is reflected in the concentrations of metalloproteinases and neurotrophic factors. Method. The concentrations of circulating MMP-1, MMP-2, MMP-9, TIMP-1, BDNF, GDNF, and VEGF were measured in 17 patients with TS. The control group was composed of 11 girls with nonpathologic short stature and normal karyotype. Results. There were no differences in chronological or bone age. No significant differences were observed in mean weight, although the Z-score BMI was higher in the study group. The mean baseline values of MMP-1 and BDNF were significantly lower in the control group than in the study group (p<0.001, p=0.001). Regression analysis revealed a positive correlation between MMP-1 concentrations and Z-score BMI (r=0.36, p=0.047) and between BDNF and Z-score BMI (r=0.48, p=0.013). Conclusion. Our pilot study showed that MMP-1 may be a potential indicator of a higher risk of cardiometabolic complications in girls with TS. The elevated concentrations of BDNF in normal-weight girls with TS need to be studied further, taking into consideration the influence of estrogen-androgen imbalance.